Подвиг стюардессы: [О. Н. Курченко] / А . А. Артамонов - Артамонов Альфред Александрович (Удмуртия, 1990)
Экземпляры: (20180511) / Инвентарный номер: 27089 / Цена: 0.20 / Сис.шифр: 66.3(2)61 / Авт.знак: А86 / ББК: 66.3(2)61